The Impacts of Maqasid Shariah in Takaful Industry: The Case of Underwriting in Auto Takaful Products - Salman, Lambak; Hartini, Ab Ghani (2016)
Islamic finance consists of Islamic banking, Islamic insurance and Islamic capital market. Being one of the major elements, Takaful (Islamic insurance) does have a significant role in the industry. The concept of Takaful is where a group of people participate in a scheme that enables them to share the burden of any risks or misfortunes faced by any of the participants/policyholders, and where appropriate, compensation are paid using the funds contributed by the participants. As far as Takaful operators are concerned, the protection of human intellect, human property and human life is directly related to the provision of Takaful service. These are in line with the principles laid down by the maqasid shariah (higher objective of Islamic law) which can be classified into five dimensions: (1) protection of religion; (2) protection of life; (3) protection of intellect; (4) protection of lineage; and (5) protection of property. Despite of the principles, the rapid growth in Takaful industries worldwide has brought in the escalating claim ratio, particularly in auto related Takaful products. As a result, Takaful operators reacted undifferentiatedly as conventional insurance towards the result by imposing strict acceptance on numerous adverse risks so called nonstandard risks. Although this reaction is reckoned as a prudent risk management measures, it contradicts with the underlying principles in maqasid shariah. Hence, this paper will focus on qualitative research methods in examining various related risks classified as substandard by Takaful operators in Malaysia and analyze the impact of maqasid shariah through various classical and contemporary opinions of Muslim scholars towards managing the identified risks.